Implementing peer support work in mental health care in Germany: The methodological framework of the collaborative, participatory, mixed‐methods study (ImpPeer‐Psy5) - Sebastian vonPeter; Ute Maria Kraemer; Lauren Cubellis; Georgia Fehler; Guillermo Ruiz‐Pérez; Daniela Schmidt; Jenny Ziegenhagen; Madeleine Kuesel; Susanne Ackers; Candelaria Mahlke; Lena Nugent; Imke Heuer (Wiley, 2024)
Abstract Background Starting in the 1990s in the United States, individuals with lived experience of mental health crises and recovery have been employed as peer support workers (PSWs) internationally. However, the implementation of PSW in clinical contexts remains challenging. Methods This manuscript presents and discusses the methodological framework of the ImpPeer‐Psy5 study on the PSW implementation in the German mental healthcare sector. This study used a mixed‐methods and collaborative research approach, as well as participatory research strategies. After describing the study design, populations, teamwork and assessments, the epistemic challenges of its methodological framework will be critically discussed and how it has iteratively shaped the object of study. Discussion and Practical Implications The healthcare, policy and funding context of PSW implementation as well as the study's methodological framework have differently influenced the ways in which the implementation of PSW has been conceived in this study. The choice of a collaborative or participatory methodological framework is advised to better align research questions and procedures to the specific needs and challenges of PSWs and other stakeholders concerned with PSW implementation. Patient and Public Contribution The research team of the ImpPeer‐Psy5 study was collaboratively staffed by a portion of researchers who also identify as users or survivors of psychiatric services. A nonprofit organization for the training of PSWs served as a practice partner throughout the research process. Different participatory formats involve a significant number of diverse stakeholders relevant to PSW implementation.